New Risks Ahead : The Eastward Enlargement of the Eurozone - Michael Bolle; Christian Fahrholz; Hanns-Dieter Jacobsen; Thomas Meyer (Free University Berlin, Jean Monnet Centre of Excellence, 2001)
Eastward enlargement is one of the hot topics in European economics. The accession of central and eastern European Countries (CEEC) into the European Union (EU) is accompanied by an extension of the eurozone to this region. This paper surveys likely outcomes and challenges of this specific feature of EU enlargement. Moreover, the article represents the start of an international research project dealing with these questions. Research is structured along different markets. Hence, the impact of an adoption of the euro is analysed for capital and labour markets as well as with respect to exchange rate and monetary policies. Our main position is that the euro has in general beneficiary effects for the CEEC and the current EU in all examined markets. However, these benefits evolve mainly in the long run, whereas the short-term costs of adaptation to the new situation may be high. Although we believe that the present value of long-term benefits exceeds these costs, it is by no means clear that policy-makers will share this view. Due to the usual political-economy transformation, the assessment of costs and benefits may be different for politicians than compared to any overall perspective. If official policies become unforeseeable, so will private behaviour. International investors may reverse their capital flows, draining precious liquidity, and leading to currency and financial crises whenever they perceive the authorities' commitment to EMU less credible. This article highlights some thinkable mechanisms how any such crisis could evolve. It, thus, sets the agenda for further research, mainly, with the focus on appropriate policy strategies to keep adaptation costs as low as possible, minimise other external risks, without hampering the long-term benefits.
Keywords: G3; E6; E0; 330; EMU; EU enlargement; monetary integration; EU-Erweiterung; Konvergenzkriterien; EU-Beitrittskriterien; Europäische Wirtschafts- und Währungsunion; EU-Staaten; Osteuropa